IMPLEMENTASI PENDIDIKAN INKLUSI DI SEKOLAH MONTESSORI DEPOK - Miftahul, Ananda; Lestari, Diana; Aminie, Aisya; Ila, Nova (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
This research is motivated by observational data that shows how to teach and teach inclusive learning. The method that is relevant for ABK students is the Montessori method, because they need objects that can be seen and felt (concrete) to focus their attention. This research uses qualitative methods, the techniques we use in collecting data are observation, interviews and documentation. The objectives of this research are as follows: 1.) Knowing the planning of inclusive education in Depok Montessori schools, 2.) Knowing the implementation of inclusive education in Depok Montessori schools, 3.) Knowing the evaluation of inclusive education in Depok Montessori schools. This research was conducted on Friday 31 May 2024 at the Depok Montessori school. The research subjects are three students with special needs and the research object is the implementation of inclusive education in the school. With a variety of methods and media, the development of students with special needs can be proven. However, during learning there are students who like to shout, resulting in a less conducive learning atmosphere. Teachers also provide policies to ABK students by teaming them with regular students to study together, so that they can socialize with other students